LITERATURE REVIEW : MANFAAT PIJAT PERINEUM UNTUK MENGURANGI RISIKO TERJADINYA LASERASI PERINEUM SAAT PERSALINAN - Ni Made Desi Dwijayani; Gusti Ayu Eka Utarini; Ni Wayan Suarniti (Jurnal Kesehatan Ilmiah Aufa Royhan, 2026)
Perineal rupture is a common complication of vaginal delivery, especially in primiparas. It can occur spontaneously (laceration) or through an episiotomy. Prevention can be achieved through Kegel exercises, optimal holding positions, prenatal yoga, and perineal massage. Perineal massage is a technique used to massage the perineal area from the third trimester of pregnancy until several weeks before delivery to increase tissue elasticity. Perineal massage is believed to increase the elasticity of the perineal muscles and tissues, thereby minimizing trauma during childbirth.The purpose of this study was to analyze the effectiveness of perineal massage in reducing the risk and severity of perineal rupture. An electronic literature search was conducted in PubMed, Google Scholar, and Scopus for the period 2020–2025 using the keywords "pijat perineum," "perineal massage," "perineal rupture," and "persuspit". Of the seven journals analyzed, perineal massage was shown to significantly reduce the incidence of second- and third-degree perineal rupture by 20–30% and increase maternal satisfaction during childbirth. Regular perineal massage performed by pregnant women in their third trimester has been shown to reduce the incidence of perineal rupture compared to those who did not perform perineal massage. Perineal massage is effective in reducing the incidence of perineal rupture during vaginal delivery. Perineal massage can be recommended as a non-pharmacological intervention for pregnant women in their third trimester to help prepare for a safer and more comfortable delivery.